Surmounting stereotyping of international students - Jamaluddin, Aini Syahira; Idrus, Faizah (Academy Publication, 2021)
This study attempted to investigate the experiences of international students towards stereotyping inside and outside of the campus. The purpose of this study was to explore the students’ experiences on stereotyping and employed qualitative method as the mode of inquiry. Semi-structured interview was conducted with five postgraduates’ students in one of the public universities in Malaysia. The respondents came from different countries and majors of studies. Finding from the study found that international students did experience stereotyping, but this encounter seemed not to affect their studies. Finally, future researchers are encouraged to adapt this study within a larger group of respondents to examine its confirmability and credibility. A careful exploration of stereotype in the areas of intercultural and cross-cultural communication among international students may provide more insights into their wellbeing in countries away from home.